STUDI EMPIRIS FAKTOR YANG BERPENGARUH TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - MICHELL SUHARLI; AWALIAWATI RACHPRILIANI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2006)
The study aims to investigate company in reporting the financial report to public. Financial statement timeliness is performance responsibility report of management to it's stockholders. The research analyses the financial report timeliness factors namely especially are variable liquidity, profitability, shareholder's dispersion, and the use of the big four public accountant. The research examined linier regression. The research found that financial statement timeliness is dependent variable. Variable liquidity, profitability, shareholder's dispersion, and the use of the big four accountant can be used are independent variable. The result of this research shows that liquidity, profitability, and the use of the big four accountant are significantly effect the timeliness to report financial statement. As shareholder's dispersion is not significantly effect the timeliness to report financial statement timeliness.